The War Between Faith and Fact. Issue 2 (2nd April 2016) - Peters, Ted
ABSTRACT: Is there a war going on between science and religion or not? The Center for Theology and the Natural Sciences and many other bridge-building advocates deny that a war must be fought between genuine science and authentic faith. Yet, a new book, Faith vs. Fact, by Jerry Coyne, launches a new attack against those with faith in God. This essay asks whether such an attack comes from genuine science or from scientism—a materialist ideology that claims rational science as its ally.